The evolution and sustainability of seasonal migration from Poland to Germany: From the dusk of the 19th century to the dawn of the 21st century - Ewa Kepinska; Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
We document and suggest a rationale for the durability of seasonal migration from Poland to Germany, a phenomenon persisting for more than a century. We refer to the role of the tradition of engaging in seasonal migration as a force that helped invigorate the process and contribute to its sustainability even when, to different degrees and at different times, the process was interrupted by a shifting political, regulatory, and legal environment. Evidence in support of the role of tradition is provided, among other things, by the continuation of the seasonal flow of migrants from once border regions - which became internal regions following WWII, despite the fact that since the redrawing of the German-Polish border, proximity is no longer a factor encouraging repeated, short-term seasonal moves.
urn:nbn:de:bsz:21-opus-67906
Keywords: F22; J22; J43; J61; N3; N33; N34; N93; N94; 330; Poland-to-Germany seasonal migration; Evolution of seasonal migration; Longterm durability of seasonal migration; Tradition